2021
DOI: 10.1097/qai.0000000000002655
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Improvement in Metabolic Health Parameters at Week 48 After Switching From a Tenofovir Alafenamide–Based 3- or 4-Drug Regimen to the 2-Drug Regimen of Dolutegravir/Lamivudine: The TANGO Study

Abstract: Baseline Metabolic Characteristics of the TANGO Safety Population Parameter 2DR (N=369) 3/4DR (N=371) a Weight, n 369 370 Mean (SD), kg 81.18 (15.35) 81.71 (15.91) Lipids, n 305 300 TC, mean (SD), mmol/L 5.01 (0.96) 4.94 (1.00) LDL-C, mean (SD), mmol/L 2.95 (0.81) 2.92 (0.87) HDL-C, mean (SD), mmol/L 1.38 (0.39) 1.36 (0.36) TC to HDL-C ratio, mean (SD) 3.86 (1.12) 3.88 (1.27) Triglycerides, mean (SD), mmol/L 1.57 (1.12) 1.49 (0.98) Fasting glucose and HbA 1c , n 358 360 Glucose, median (range), mmol/L 5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 24 publications
4
25
0
Order By: Relevance
“…Similar observations have been reported in individuals with and without ≥10% weight gain commencing dolutegravir [ 8 ]. In line with our results, small increases in triglycerides, total cholesterol, and LDL cholesterol following switch to TAF—either with or without an INSTI and irrespective of weight change—have been reported previously [ 3 , 38 ]. The impact of such minor changes in metabolic parameters on the long-term risk of cardiovascular disease and diabetes remains to be determined.…”
Section: Discussionsupporting
confidence: 93%
“…Similar observations have been reported in individuals with and without ≥10% weight gain commencing dolutegravir [ 8 ]. In line with our results, small increases in triglycerides, total cholesterol, and LDL cholesterol following switch to TAF—either with or without an INSTI and irrespective of weight change—have been reported previously [ 3 , 38 ]. The impact of such minor changes in metabolic parameters on the long-term risk of cardiovascular disease and diabetes remains to be determined.…”
Section: Discussionsupporting
confidence: 93%
“…Several switch studies of dolutegravir plus lamivudine included in this analysis reported increases in creatinine levels [ 52 , 69 ] and decreases in calculated creatinine clearance [ 36 , 60 , 70 , 77 ], consistent with the known, non-pathological inhibitory effect of dolutegravir on creatinine secretion [ 78 ]. This analysis showed that switching to dolutegravir plus lamivudine was generally associated with minimal impact or improvements in total cholesterol and triglycerides, consistent with outcomes reported in the phase III TANGO study [ 27 , 79 ]. Although real-world studies reporting on BMD outcomes with dolutegravir plus lamivudine are limited, two studies reported improvements in BMD after switching to dolutegravir plus lamivudine [ 71 , 72 ], including in PWH previously on tenofovir disoproxil fumarate-containing regimens, which have been shown to negatively affect BMD [ 80 ].…”
Section: Discussionsupporting
confidence: 78%
“…Borghetti et al 31 studied the metabolic changes in virologically suppressed patients who switched to the 3TC + DTG dual therapy and found that this regimen improved their overall lipid profile; the LDL-C, total cholesterol, and triglyceride levels decreased by 15 mg/dL (P = 0.009), 24 mg/dL (P , 0.001), and 66 mg/dL (P , 0.001), respectively. The TANGO trial also drew a similar conclusion with respect to lipid metabolism, 32 with the dual therapy of 3TC + DTG inducing a higher degree of reduction in the levels of total cholesterol, LDL-C, and triglycerides than that observed with the TAF-based regimen (all P , 0.001). In our study, the overall incidence rate of grade 1 and 2 adverse events associated with LDL-C was 13.4% higher than the baseline value (P = 0.007), but their total cholesterol and triglyceride levels did not change significantly compared with the baseline values, these results probably because the abnormalities in lipid metabolism were diagnosed during the 24-week follow-up rather than at the end of the follow-up (week 24).…”
Section: Discussionmentioning
confidence: 71%